MODEL JARINGAN UTILITAS TERPADU BAWAH TANAH DI KOTA BANJARBARU - Ahmad Banin; Mahmud Mahmud; Akhmad Rizali; Danang Biyatmoko (EnviroScienteae, 2017)
Banjarbaru has prepared as the capital of South Kalimantan which has a barometer was grown as the center of government, economic, education and services, so it can be a magnet for people who wants to get their opportunity. This situation should become to increase facilities and infrastructure to support the activities and movements of populations. It can make governments gets many tasks. The research aims to know the effectiveness of existence and give a solution or the alternative model to handle the utility of underground network in Banjarbaru, for the future from management and institution mainly. This problem is interesting to study as material for making an integrating model for the utility of underground network continuously. The experiment was conducted by using Qualitative methods. Data was collected by direct observation, interview and questioner to strengthen the data. Then, the data was analyzed by using SWOT analysis. The result showed that the utility of underground network ( existing ) is perceived by society is not effective because it is usually digging holes in the same place for different installation. So, the management of handling in the utility of underground network should be performed or handle as integrating and professional, not detrimental and stakeholders are leaded by the government in Banjarbaru. The result also provides the solution or alternative model to gain all underground networks such as Telkom, PDAM, drainage, PLN, sanitation and gas. This model can applicate in Banjarbaru area, particularly for the government of South Kalimantan especially at offices because it was designed with environmental sustainable management.